Effects of copper bioaccumulation on growth and biochemical constituents of the seedlings of Casuarina equisetifolia L. - Kumari, B. M. Rathna (Current Botany, 2022)
Accumulation of heavy metals in the soil causes a significant impact on the biological processes in the plants. In the present study, the impact of bioaccumulation of copper (Cu) on the growth and biochemical constituents of the seedlings of Casuarina equisetifolia was assessed. The results showed that C. equisetifolia is a hyper-accumulator of Cu. The roots of the C. Equisetifolia significantly accumulated (p< 0.05) greater levels of Cu than stem and leaves. Similarly, the seedlings exposed to different concentrations of Cu showed differential height and collar diameter. The higher concentrations of Cu significantly (p< 0.05) hindered the fresh and dry weights of seedlings. It was noticed that accumulated Cu caused a significant decrease in levels of total carbohydrates, proteins and chlorophyll contents in C. equisetifolia seedlings.